The headmaster's wife - Haddam, Jane, 1951-2019- (Haddam, Jane, 1951-2019- Gregor Demarkian books, 2005)
Mark DeAvecca is a brilliant fifteen-year-old in his first year at the exclusive private academy, Windsor School. Mark, the son of noted commentator Liz Tolliver, grew up in very different circumstances and could not fit in less well. With its hundred-year-old history, Windsor is rife with tradition, nasty rumors, petty jealousies and long buried resentments. The most savage of those unpleasant undercurrents swirl around the headmaster's wife - currently rumored, with good reason, to be having an affair with Mark's roommate, a street-tough scholarship student. Mark, however, has his own problems - he feels himself slowly losing his grip on reality and the staff widely believes him to be just another prep school burnout headed for an unpleasant end. So when Mark returns from a late-winter ramble about the campus to find his roommate dead, hanging from the ceiling of their room, he's reached the end of his own metaphorical rope. Even though he's no longer sure about the line between fantasy and reality, Mark is fairly certain that something is going on at the school and there's more to the death than the official declaration of suicide. With nowhere else to turn, Mark calls retired FBI agent Gregor Demarkian to ask for help. Sensing the crisis in Mark's dulled voice, Demarkian arrives to find Mark in dire physical and mental state, and a school only too eager to sweep his roommate's death under the rug. In what quickly becomes one of the most complex and challenging cases in his career, Demarkian must untangle truth from fiction, fantasy from reality, before another life is lost.